(untitled) (Patan Pragya, 2024)
This study examines the factors that affect employees’ job satisfaction post-M&A in the Nepalese context. This study has used a descriptive survey research design. Data are collected from 340 employees across seven commercial banks that underwent M & As employing structured questionnaires. The findings demonstrate that M & As significantly affect employees’ job satisfaction. The five key factors that influence job satisfaction are career growth and advancement, remuneration and benefits, co-workers, supervision, and cultural adaptation. These factors collectively explain 41.8% of job satisfaction variability. This research serves as a vital resource for Nepalese banks grappling with the challenges presented by transformative events like M&As. investing in training and career development programs, promoting teamwork, providing leadership training, and ensuring respectful supervision can positively impact on job satisfaction.